Necessary and sufficient conditions for the successful three-phase photocatalytic reduction of CO2 by H2O over heterogeneous photocatalysts. Issue 13 (15th March 2018) - Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : Artificial photosynthesis has recently drawn an increasing amount of attention due to the fact that it allows for direct solar-to-chemical energy conversion. Abstract : Artificial photosynthesis has recently drawn an increasing amount of attention due to the fact that it allows for direct solar-to-chemical energy conversion. However, one of the basic steps of this process, namely the reduction of CO2 by H2 O to afford O2 and CO2 reduction products (CO2 RPs) such as HCOOH, CO, HCHO, CH3 OH, and CH4, is very difficult to achieve. In contrast to the CO2 reduction in plants and homogenous systems, the reduction of CO2 to CO2 RPs over heterogeneous photocatalysts was challenged by the competing reduction of H + to H2 . Unfortunately, most of the research performed so far has focused only on the reduction of CO2, rather than the characterization of the H2 O oxidation and H2 production. Moreover, the fact that the heterogeneous photocatalytic reduction of CO2 into CO2 RPs by H2 O should satisfy several selectivity criteria has often been ignored. Herein, we propose three such evaluation criteria, namely (1) the origin of carbon in CO2 RPs (determined using isotopically labeled CO2 ( 13 CO2 )), (2) the relative amount of H2 and CO2 RPs produced, and (3) the amount of O2 produced by the oxidation of H2 O. If all these criteria are satisfied, i.e., the carbons of CO2 RPs originate from CO2, the amount of H2 produced is negligible, and a stoichiometric amount of O2 is produced by the oxidation of H2 O, then CO2 introduced into the gas phase is believed to be reduced by H2 O to CO2 RPs in the aqueous phase.